Preliminary Study in Developing Traditional Street Foods as Nutrition Education Media for Indonesia Youth - Yulia, Cica; Nikamawati, Elis Endang; Widiaty, Isma (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
The unceasing globalization has a great influence on the lifestyle of the young generation of Indonesia, including habit to consumed fast food. Many research proved, fast food was not good for health. Habit of eating fast food in Indonesia increased from day to day, especially in the adolescent. This is very dangerous because not only bad for health, but also threat our culture. In general, the aim of this study was to conduct a preliminary study in order to develop traditional foods as a nutrition education media for adolescent. The study de-sign was cross sectional, the respondents were students in junior high school in Bandung. Sampling Technique done by purposive. There were 85 respondents. The results showed that the respondents' knowledge about traditional street food from Sundanese are divided into three categories. 40% had a good knowledge, 34% had fair knowledge and 26% had a poor knowledge. Perceptions of respondents about the importance of having knowledge about traditional foods is 41.2% consider it important. Perceptions of the media information that can be used to educate traditional food are posters in schools (37.65%), brochures (4.71%), computer programs (34.14%) and program /application in smart phone (23.53%).